Low-cost high performance piezoelectric fabrics based on Nylon-6 nanofibers - Kwon, Dong-Jun; Milam-Guerreroa, JoAnna; Choi, Yun Young; Myung, Nosang Vincent (Frontiers in Chemistry, 2024)
To fully harness the potential of smart textiles, it is cruical to develop energy harvesters which can function both as fabric and energy generator. In this work, we present a high performance low-cost piezoelectric nano-fabric using even-number Nylon (i.e., Nylon-6). Nylon-6 was chosen for optimal mechanical properties such as mechanical strength and stiffness. To maximize the voltage output, Nylon six nanofibers with varying diameter and crystallinity were synthesized by adjusting the polymer precursor and solvent, along with electrospinning parameters, followed by post thermal treatment. The average diameter of electrospun nanofibers was finely tuned (down to 36 nm) by adjusting solution polymer precursor content and electrospinning parameters. The content of desired piezoelectric-active γ crystal phase enhanced upto 76.4% by controlling solvent types and post thermal annealing. The highest peak to peak voltage (V33) of 1.96 V were achieved from γ-phase dominant (>60%) Nylon-6 nanofiber fabric which has an average nanofiber diameter of 36 nm with high fiber fraction (i.e., > 98%). Unlike its thin film counterpart, piezoelectric electrospun nanofiber fabric demonstrated durability against wear and washing. This work paves a new way to utilize Nylon-6 nanofibers in next-generation electronic textiles.